1973
DOI: 10.1177/104649647300400409
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Participatory Group Experience on Counselors in Training

Abstract: In recent years a great deal of attention has been given the concept of self-actualization (Maslow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Since all the groups with which I was concerned were composed of graduate students preparing to be counselors, I reviewed findings relating to similar populations. Significant gains between POI pre-test and post-test means were detected in several studies (Eiben & Clack, 1973;Maynard & Long, 1976;Shapiro & Gust, 1974).…”
Section: Growth Groups and The Personalmentioning
confidence: 87%
“…Since all the groups with which I was concerned were composed of graduate students preparing to be counselors, I reviewed findings relating to similar populations. Significant gains between POI pre-test and post-test means were detected in several studies (Eiben & Clack, 1973;Maynard & Long, 1976;Shapiro & Gust, 1974).…”
Section: Growth Groups and The Personalmentioning
confidence: 87%
“…Research studies indicate that it is far easier for students to acquire specific skills (Carkhuff, 1969;Eagan, 1975;Ivey, 1971 ; Kagan, 1975;Toukmanian & Rennie, 1975) than for them to modify their life-styles (Goldberg, 1974;Lutwak & Hennessy, 1982;Neufeldts, 1978). In general, students who have participated in a group counseling experience showed an increase in their ability to provide the core conditions of counseling but manifested only minimal personality change (Anderson, 1969;Arbuckle, 1966;Eiben & Clark, 1973;Foley & Bonney, 1966;Gazda & Bonney, 1966;Mahon & Altman, 1977;Woody, 1971). Whether the group's counseling experience helps students to improve their effectiveness as counselors has not been clearly demonstrated (Cecere, 1969;McKinnon, 1969;Nye, 1972;Ohlsen, 1975;Yalom, 1976).…”
mentioning
confidence: 92%
“…Typically, instructors require students to participate in some type of therapeutic group and use this experience as a basis for inculcating group leadership skills (Yalorn, 1975;Halgin, 1982). Although studies have shown that students who have participated in a group counseling experience increase their ability to provide the core conditions in individual counseling (Gazda & Bonney, 1966;Woody, 1971;Eiben & Clark, 1973), the influence of a group counseling experience on counselor effectiveness has not been clearly demonstrated (McKinnon, 1969;Nye, 1972;Ohlsen, 1975;Yalom, 1975). Training programs developed by Carkhuff (1969Carkhuff ( ), lvey (1971, and Eagan (1975) may increase a trainee's ability to communicate more clearly and enhance his or her self-awareness level, but these factors in and of themselves do not necessarily lead to more effective counseling (Mahon & Altman, 1977).…”
mentioning
confidence: 97%